PEMBUATAN ANTENA MIKROSTRIP MODEL ANGKA 4 UNTUK PENERIMA SINYAL TELEVISA PADA JALUR UHF (ULTRA HIGH FREKUENSI) - Lifwarda lifwarda; Firdaus firdaus (Elektron : Jurnal Ilmiah, 2013)
Development of science and technology very rapidly in various fields brought great influence to all aspects of life one of this field of telecommunications. Development of telecommunication technology that bring due faster to hight public demand for telecommunications services users get an easy and fast service are used as medium convey information One of the device in question is antenna. Many type of antennas that have been developed for the reception of televisions signals and are generally made of wires, pipes or aluminium which has large size and weight. Needed for the antenna which has advantages in terms of shape light weight small volume from that can be easily adapted to the priimary device for on the fabrication and can be used for a wide band frequency. The antenna is microstrip antennas capable adjusted in assembly or in other words easily in a microstrip antenna placement. Microstrip antenna models 4 is designed to work in the range frequency 470 – 750 MHz. This antenna has a value of more than -10 dB returnloss to a predetermined range frequency. The measurement results of the antenna resonates at a frequency of 518 MHz gain value obtained by 1 dB, and has a wide bandwidth of 7 MHz, while for polaradiasi shaped bidirectional.